Biallelic mutation of FBXL7 suggests a novel form of Hennekam syndrome. Issue 1 (21st October 2019) - Boone, Philip M.; Paterson, Scott; Mohajeri, Kiana; Zhu, Wenmiao; Genetti, Casie A.; Tai, Derek J. C.; Nori, Neeharika; Agrawal, Pankaj B.; Bacino, Carlos A.; Bi, Weimin; Talkowski, Michael E.; Hogan, Benjamin M.; et al.
Abstract: Hennekam lymphangiectasia‐lymphedema syndrome is an autosomal recessive disorder characterized by congenital lymphedema, intestinal lymphangiectasia, facial dysmorphism, and variable intellectual disability. Known disease genes include CCBE1, FAT4, and ADAMTS3 . In a patient with clinically diagnosed Hennekam syndrome but without mutations or copy‐number changes in the three known disease genes, we identified a homozygous single‐exon deletion affecting FBXL7 . Specifically, exon 3, which encodes the F‐box domain and several leucine‐rich repeats of FBXL7, is eliminated. Our analyses of databases representing >100, 000 control individuals failed to identify biallelic loss‐of‐function variants in FBXL7 . Published studies in Drosophila indicate Fbxl7 interacts with Fat, of which human FAT4 is an ortholog, and mutation of either gene yields similar morphological consequences. These data suggest that FBXL7 may be the fourth gene for Hennekam syndrome, acting via a shared pathway with FAT4 .